Pengaruh Profil Pelajar Pancasila Terhadap Karakter Religius Siswa di Madrasah Ibtidaiyah - Rofi'ah, Siti; Rohimah, Fina (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
Using an associative quantitative method, this study aims to analyze the influence of the Pancasila student profile on the religious character of students in Islamic Elementary Schools (Madrasah Ibtidaiyah). Religious character plays a role in shaping a generation of young people with noble morals. The Pancasila student profile, which includes the values of religiosity, nationalism, mutual cooperation, integrity, independence, and global diversity, is believed to be a foundation in the development of students' character. The sample for this study consisted of 33 students from MI Al Asy’ari using a saturated sampling technique because the entire small population became research participants. Data were collected using a questionnaire and analyzed with the Spearman correlation test. The results showed a significant influence between the Pancasila student profile and religious character with a hypothesis test significance value of 0.00 < 0.05. The contribution magnitude was shown through the determination coefficient test with an R square value of 0.403, which means the Pancasila student profile contributes 40% to the variation in religious character, while the remaining 60% is influenced by other factors. This study concludes that integrating Pancasila values into learning in Madrasah Ibtidaiyah effectively enhances the religious character of students. maximum 200 word abstract in English in italics with Verdana Pro Cond Light, 12 point. The abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection of research topics, research methods and a summary of the results. The abstract should end with a comment about the importance of the results or conclusions brief.